STUDENTS' NECESSITIES, LACKS AND WANTS ON ICT-BASED ENGLISH FOR NURSING STUDENTS - Risa Arroyyani; Lusi Nurhayati (English Department, University of Riau Kepulauan, Batam,Indonesia, 2019)
This study aims at gathering information about necessities, lacks, and wants of the students on ICT-based English for Nursing Students materials as a part of needs analysis with a descriptive qualitative method. The subject was the students of Nursing Department. The data were obtained from primary sources including a questionnaire (both closed-ended and open-ended questionnaire) and secondary sources including an observation. The results of this study showed that (1) students' necessities on ICT-based English for Nursing Students materials were for communication purposes in daily life both written and spoken; (2) the lacks of ICT knowledge were the abilities to operate the media and technology applications in the learning process; of language skill were a communication skill and an understanding for the language used on website or application, (3) students’ wants on ICT based English for Nursing Students materials were proper internet facilities in campus, supporting teaching and learning facilities, Web and online-based learning activities, and online-based assessments and grades. All shows that students are welcome to the use of ICT-based learning materials in the classroom at a moderate level.